Radiation Shielding Properties of SiO2–МеIIFe12O19 Nanocomposite Materials Prepared by Sol-Gel Method - Kapshai, M.N.; Gaishun, V.E.; Nasonova, N.V. (Хімія, фізика та технологія поверхні, 2010)
SiO2 materials containing different magnetic fillers МеIIFe12O19 are obtained by the sol-gel method. It is studied the weakening of electromagnetic radiation in the frequency range 8–11.5 GHz by the materials obtained with the use of panoramic attenuation measurers and panoramic standing wave voltage coefficient measurers. It is also estimated the attenuation contribution of the radiation reflection from the material surface. The materials obtained can be used as a first layer of electromagnetic radiation absorbing materials which reduce the level of reflected energy Золь-гель методом отримані SiO2 матеріали, що містять різні магнітні наповнювачі МеIIFe12O19. З використанням панорамних вимірювачів ослаблення та панорамних вимірювачів коефіцієнта стоячої хвилі за напругою вивчене ослаблення ними електромагнітного випромінювання в діапазоні частот 8…11,5 ГГц. Оцінено внесок відбиття від поверхні матеріалу в ослаблення випромінювання. Отримані матеріали можуть бути використані в якості першого шару радiопоглиначiв електромагнітного випромінювання, яке знижує рівень енергії, що відбивається. Золь-гель методом получены SiO2 материалы, содержащие различные магнитные наполнители МеIIFe12O19. С использованием панорамных измерителей ослабления и панорамных измерителей коэффициента стоячей волны по напряжению изучено ослабление ими электромагнитного излучения в диапазоне частот 8…11,5 ГГц. Оценен вклад, вносимый отражением от поверхности материала, в ослабление излучения. Полученные материалы могут быть использованы в качестве первого слоя радиопоглотителей электромагнитного излучения, снижающего уровень отражаемой энергии.